Les transformations d'un mythe d'origine L'exemple de Gengis Khan et de Tamerlan - Denise Aigle (Revue des Mondes Musulmans et de la Méditerranée)
The representation of Chinggis Khan, the great conqueror and founder of a dynasty is closely related to that of the mythical hero. His life is marked by many signs, characteristic of an uncommon destiny. In particular, his birth is presented as a miraculous event though its story has been changed in the course of time as his descendants and later his epigones drifted away from Shamanist Mongol origins. The story of Chinggis Khan's birth is first related to the Mongol myth of origins according to which the Mongols descend from « Blue-Wolf and " Fawn-Doe ", this story itself being evidently inspired by the Turkish myth. The Secret History of the Mongols, written some time after Chinggis Khan's death, suggests that his ancestor, the widow Alan-Qo'a, had been fertilised by a creature who « crept like a yellow dog ». Such a part played by an animal is in accordance with the fact that shamanism is based on a system of interrelations between the animal and human worlds. Some decades later, Rashid al-din'sJâmi' al-tawârikhtakes the same legend up again, but mentions only a « fawn creature ». Later, animal connections completely disappear in a Muslim context totally detached from shamanist references. In the first half of the 15th century, the inscriptions copied in the mausoleum of Tamerlane mention a luminous ray manifested under the shape of an « accomplished mortal being », descendant of 'All. Lastly, in Moghul India, Chinggis Khan is explicitly related to Jesus when the author of the Akbar-näma writes that his ancestor got pregnant in the same way as Maryam did.